2022
DOI: 10.1021/acs.jpclett.2c02286
|View full text |Cite
|
Sign up to set email alerts
|

Quantum State-to-State Rates for Multistate Processes from Coherences

Abstract: For a multistate system coupled to a general environment through terms local in the system basis, we show that the time derivatives of populations are given in terms of imaginary components of coherences, i.e., off-diagonal elements of the reduced density matrix. When the process exhibits rate dynamics, we show that all state-to-state rates can be obtained from the early “plateau” values of these imaginary components. The evolution of the state populations is then obtained from the short-time simulation result… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
25
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(25 citation statements)
references
References 40 publications
0
25
0
Order By: Relevance
“…This has recently been successfully applied to investigations of multistate problems. 23 However, here we are not interested in a rate perspective. We rather want to understand the full time dynamics with additional information about the channel-dependent contributions.…”
Section: Methodsmentioning
confidence: 99%
“…This has recently been successfully applied to investigations of multistate problems. 23 However, here we are not interested in a rate perspective. We rather want to understand the full time dynamics with additional information about the channel-dependent contributions.…”
Section: Methodsmentioning
confidence: 99%
“…In recent work we showed that the rate of population change is related to the imaginary parts of the coherences through the expression normald normald t ρ̃ k k ( t ) = 2 normalℏ j = 1 n H j k normalI normalm ρ̃ j k ( t ) where H j k are the matrix elements of the bare system Hamiltonian, eq . Equation is exact, regardless of the form of the bath Hamiltonian, as long as the system-bath coupling is diagonal in the system basis.…”
Section: General Features Of Coherence Mapsmentioning
confidence: 99%
“…Imaginary Components of Coherences. In recent work 18 we showed that the rate of population change is related to the imaginary parts of the coherences through the expression…”
Section: General Features Of Coherence Mapsmentioning
confidence: 99%
“…The usual practice is to focus the numerical studies on the evolution of the population in the excited states of each of the chromophores. Here, we additionally use the recently developed coherencebased analytic techniques [43][44][45][46] to unravel the pathways that the excitation takes and the impact of the vibrational modes. Baker and Habershon [47] have explored these pathways in FMO using the Lindblad master equation.…”
mentioning
confidence: 99%
“…Wu et al [43] have built flux networks to analyze the flows along different pathways. More recently, Dani and Makri have shown that the time-derivative of the on-site populations is related to linear combinations of the off-diagonal terms of the reduced density matrix [44], and visualized the coherences in forms of maps that encode information about the dynamics of the system [45]. We extended these ideas to partition the time-dependent population change on a site in terms of transport along different state-to-state channels, which is useful for understanding the instantaneous population transfer in these systems with complex interconnects [46].…”
mentioning
confidence: 99%